Pengembangan Madrasah sebagai Pendidikan untuk Semua - Muzhoffar Akhwan (Islamic University of Indonesia, 2008)
Since the early 20th century, madrasah with its independent characteristics is accepeted by people gradually, as one of the Islamic education which plays an important role in the development and improvement of education quality in Indonesia. However its existence which is managed by people as much as 96% made it difficult to get its right to be supervised based on the letter of dicision from the Ministry of Religion. The government’s aid is very important for process of modernizing the school. The madrasah system was related to the school Islamic identity in facing the competition of education in global era.Keyword: Islamic education, madrasah, education quality.